2021
DOI: 10.1158/1078-0432.ccr-20-3453
|View full text |Cite
|
Sign up to set email alerts
|

177Lu-DOTA-EB-TATE, a Radiolabeled Analogue of Somatostatin Receptor Type 2, for the Imaging and Treatment of Thyroid Cancer

Abstract: We demonstrated that somatostatin receptor type 2 (SSTR2) may serve as a molecular target in the diagnosis and treatment of a subset of thyroid cancer (TC) patients. We showed that TC lesions have higher SSTR2 expression than normal thyroid. Further, we reported high uptake of SST analog 68 Ga-DOTA-TATE in a subset of TC patients, particularly in Hurthle-cell TC resistant to standard treatment. In vivo studies demonstrated that the theranostic efficacy of SST analogs could be enhanced by utilizing radiolabeled… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…SSTR2, as a G protein-coupled cell surface receptor, can be activated by extracellular ligands, which leads to the inhibition of cell proliferation ( Lechner et al, 2021 ). Precious studies demonstrated that SSTR2 might serve as a molecular target in the diagnosis and treatment of thyroid cancer ( Thakur et al, 2021 ), small intestinal neuroendocrine tumor ( Elf et al, 2021 ), and neuroendocrine tumors ( Si et al, 2021 ). VIP can provide protection from apoptosis in tumorigenesis ( Sastry et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…SSTR2, as a G protein-coupled cell surface receptor, can be activated by extracellular ligands, which leads to the inhibition of cell proliferation ( Lechner et al, 2021 ). Precious studies demonstrated that SSTR2 might serve as a molecular target in the diagnosis and treatment of thyroid cancer ( Thakur et al, 2021 ), small intestinal neuroendocrine tumor ( Elf et al, 2021 ), and neuroendocrine tumors ( Si et al, 2021 ). VIP can provide protection from apoptosis in tumorigenesis ( Sastry et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, compared to normal thyroid tissue, expression of mRNA was significantly upregulated for SSTR2 in PTC, and for SSTR3 in PTC and ATC, while SSTR5 expression was non-significantly elevated in PTC and FTC. Our group also demonstrated a higher expression of SSTR2 in all types of thyroid cancers compared to normal thyroid based on immunohistochemical analysis of surgical tumor specimens obtained from patients with thyroid cancer ( 70 ). Furthermore, we identified in vivo uptake of 68 Ga-DOTATATE in different thyroid cancers ( 70 ).…”
Section: Prrt In Thyroid Cancersmentioning
confidence: 59%
“…Our group also demonstrated a higher expression of SSTR2 in all types of thyroid cancers compared to normal thyroid based on immunohistochemical analysis of surgical tumor specimens obtained from patients with thyroid cancer ( 70 ). Furthermore, we identified in vivo uptake of 68 Ga-DOTATATE in different thyroid cancers ( 70 ). While the maximum standardized uptake value (SUV max ) was variable in PTCs and MTCs, the highest SUV max values were observed with HTCs.…”
Section: Prrt In Thyroid Cancersmentioning
confidence: 59%
“…These agents can be linked to radionuclides like 68-gallium (68Ga) and 177-lutetium (177Lu) for both imaging and therapeutic applications respectively. For instance, Thakur et al found that SSTR2 is higher expressed in thyroid carcinomas and medullary carcinomas than in normal thyroid tissue and most patients with metastatic thyroid cancer showed positive 68Ga-DOTATATE uptake indicating that SSTR2 is expressed by these tumors (28). Treatment of mice with 177Lu DOTATATE resulted in tumor growth reduction (28).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Thakur et al found that SSTR2 is higher expressed in thyroid carcinomas and medullary carcinomas than in normal thyroid tissue and most patients with metastatic thyroid cancer showed positive 68Ga-DOTATATE uptake indicating that SSTR2 is expressed by these tumors (28). Treatment of mice with 177Lu DOTATATE resulted in tumor growth reduction (28). Furthermore, in a randomized, placebo-controlled study of the somatostatin analogue lanreotide in patients with SSTRpositive (by scintigraphy) grade 1 or 2 neuroendocrine tumors with a Ki-67 proliferative index of <10% originating in the pancreas, midgut, or hindgut or of unknown origin lanreotide treatment was associated with significantly prolonged progression-free survival of 65% at 24 months when compared to 33% for the placebo group (29).…”
Section: Introductionmentioning
confidence: 99%